Uznanie państwa. Między teorią a praktyką - Kułaga, Łukasz (Kwartalnik Prawa Publicznego, 2012)
Purpose of this article is to reevaluate current doctrine on recognition of states in international law, by comparing legal ideas with practice of states, particularly the new one regarding Kosovo, Abkhazia, South Ossetia, South Sudan and Palestine. Legal assessment of unilateral declaration of Kosovo by International Court of Justice not only brought several thought provoking opinions, but also enabled states to bring to public attention their positions on recognition of states. Article identifies major issues related to recognition i.a. methods of recognition, question of right or obligation to recognize, conditionality of recognition, and last but not least possibility of withdrawal of recognition. Author deals also with to most crucial theories related to legal effects of recognition of states – constitutive and declaratory theory. He presents the opinion that neither of this important legal ideas – in a pure form – is appropriate for explaining process of admitting new states to international society. Thus a third way is proposed. Recognition alone do not create state… nonetheless it is one of the key factors for its creation. When there is no clear international law obligation not to recognize indicated for example by the UN Security Council, individual or collective recognition should be considered as an important factor of assessing effectiveness of emerging territorial entity. Lack of sufficient recognition by international community makes it unable for entities to participate in international legal order even when they hold effective control over territory and its population. Somaliland and Taiwan can be considered as the most prominent examples in this regard.